Longitudinal study of lung function in coal-miners. - Love, R G (1982)
Longitudinal loss of lung function in 1677 coal-miners from five British collieries has been calculated from the results of serial cross-sectional epidemiological surveys and compared with measured concurrent individual respirable dust exposures and partially estimated previous cumulative exposures. Loss of forced expired volume in one second (FEV1) over approximately 11 years was found to increase with previous cumulative dust exposure after allowing for the effects of age, height, smoking, and overall colliery differences. This relationship was found to hold with concurrent dust exposure only when colliery differences were ignored. These results confirm by direct measurement inferences drawn indirectly from previous cross-sectional studies of the relationship between FEV1 and dust exposure.